The crisis, policy reactions and attitudes to globalization and jobs - David N. F. Bell; David G. Blanchflower (Institute for the Study of Labor (IZA), 2011)
We consider the effects of the financial crisis and subsequent recession on world labour markets. It begins by cataloguing the adverse effects on output of the sudden collapse in demand brought about by the financial crisis in what has come to be called the Great Recession. Next we look at the labour market and how employment and unemployment have been impacted and document the very different responses by country. We then move on to look at attitudinal indicators of the impact of the rising levels of joblessness we observe across most OECD countries. We examine data on well-being and on attitudes to employment. We also examine a number of questions about the impact of globalization that respondents across many European countries were asked in the Spring of 2010. Finally, we examine the policy responses of governments, and consider what lessons might be learned from the marked differences in labour market outcomes following the recession.
urn:nbn:de:101:1-201105173162
Keywords: J31; J64; 330; globalization; jobs; Finanzmarktkrise; Konjunktur; Weltkonjunktur; Arbeitsmarkt; Beschäftigungseffekt; Zufriedenheit; Wirtschaftspolitik; OECD-Staaten